Kummoona Chondro-Ossous graft good substitute to condylar growth center and fore correction of facial deformity in chilidren - Raja Kummoona (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2017)
Kummoona Chondro-Ossous graft is the most popular graft been used for reconstruction of the temporomandibular joint for restoring growth, repair and remodeling and fore correction of facial deformity in children with restoration of functional activity of the damaged temporomandibular joint (TMJ) and graft work as primary growth center. These graft been studied by experiment on Rabbits as an excellent animal model for viability of the graft. clinically 36 cases were reported, they were 25 children including 9 females and sixteen boys with history of ankyloses of the TMJ and ten children of 4 females and 6 boys suffering from milled hemi facial microsomia or fi rst arch dysplasia syndrome and one female case with traumatic hypoplasia of the condyle.  Fellow up of the cases from 3-5 years and graft does not showed any ossifi cation or chondrifacation beside its function for restoring growth, remodeling and repair on the long run.